EU demand for defense, 1990-2019: A strategic spatial approach - Justin George; Todd Sandler (Games, 2021)
For 1990-2019, this study presents two-step GMM estimates of EU members' demands for defense spending based on alternative spatial-weight matrices. In particular, EU spatial connectivity is tied to EU membership status, members' contiguity, contiguity and power projection, inverse distance, and arms trade. At a Nash equilibrium, our EU demand equations are derived explicitly from a spatially based game-theoretical model of alliances. Myriad spatial linkages among EU members provide a robust free-riding finding, which differs from the spatial and non-spatial literature on EU defense spending. Even though the EU applies common trade policies and allows for unrestricted labor movement among members, members' defense responses adhered to those of a defense alliance. Moreover, EU defense spending exhibits positive responses to GDP and transnational terrorist attacks, and a negative response to population. During the sample period, EU members did not view Russia as a military threat.
Keywords: D74; H41; C21; 330; alliance; European Union (EU); Nash equilibrium; spatial autoregression and connectivity; strategic free riding